PERANAN MAHASISWA MENGIMPLEMTASIKAN LITERASIBAHASA MELALUI PROGRAM KAMPUS MENGAJAR DI SEKOLAH DASAR NEGERI 200207 PADANGSIDEMPUAN - Elizon Nainggolan; Binur Yuni Arta; Sani Susanti (Universitas Negeri Medan, 2022)
Abstrac : Student's Role In Implementing Literature Through Campus Teaching Programat Padangsidempuan 200207 Public Elementary School. Language literacy skills are one of the fundamentals of the future inevitability needed by the information society era. The low culture of language literacy in Indonesia is one of the factors for holding Campus Teaching activities by the Ministry of Education and Culture in the Independent Learning Campus program with students from different universities as the main movers. The purpose of this manuscript is to determine the role of students in strengthening and developing language literacy in students at the Mengjar Campus program school, one of which is Padangsidempuan 200207 Public Elementary School. The method used is a qualitative descriptive approach where students through experience have played an active role as teachers of language literacy drivers, have conducted document analysis, guided discussions and interactive data analysis. Through the Teaching Campus program, it is hoped that students at Padangsidempuan 200207 Public Elementary School will be more enthusiastic about reading because the teaching given by students pays more attention to psychological aspects and interesting learning media to adapt to the ongoing pandemic situation.Keywords : campus teaching, independent learning, literacy, elementary schoolAbstrak : Peranan Mahasiswa Dalam Mengimpelemtasikan Literasi Melalui Program Kampus Mengajar Di Sdn 200207 Padangsidempuan. Kemampuan literasi bahasa adalah salah satu fundamental dari keniscayaan masa depan yang dibutuhkan oleh era masyarakat informasi. Budaya literasi bahasa yang rendah di Indonesia merupakan salah satu faktor diadakannya kegiatan Kampus Mengajar oleh Kementrian Pendidikan dan Budaya dalam program Mandiri Belajar Kampus Merdeka dengan mahasiswa dari Pergururan Tinggi yang berbeda sebagai penggerak utama. Tujuan dari naskah ini adalah untuk mengetahui peran mahasiswa dalam penguatan dan pengembangan literasi bahasa pada siswa di sekolah program Kampus Mengjar yang salah satunya adalah SD Negeri 200207 Padangsidempuan. Metode yang digunakan adalah pendekatan deskriptif kualitatif dimana mahasiswa melalui pengalaman telah berperan aktif sebagai pengajar penggerak literasi bahasa sudah melakukan analisis dokumen, diskusi terpimpin dan analisis data interaktif. Melalui program Kampus Mengajar, diharapkan siswa di SD Negeri 200207 Padangsidimpuan lebih antusias membaca karena pengajaran yang diberikan oleh mahasiswa lebih memerhatikan aspek psikologis dan media pembelajaran yang menarik untuk menyesuaikan dengan situasi pandemi yang berlangsung.Kata kunci : Kampus Mengajar, Merdeka Belajar, Literasi, Sekolah Dasar